Decomposição térmica do bicarbonato de sódio: do processo Solvay ao diagrama tipo Ellingham - Maia,Alessandra de Souza (2003)
A didactic experiment based on the thermal decomposition of sodium bicarbonate using a reagent found in the marketplace is proposed. The reaction products are identified by qualitative tests and stoichiometric calculations. The thermal stability of carbonates and the influence of lattice energies are discussed, emphasizing periodic trends in the alkali and alkaline earth families. The industrial importance of the reaction is also explored.